Brown Baby Jesus: The Religious Lifeworlds of Canada's Goan and Anglo-Indian Communities - Carriere, Kathryn F. M. (Université d'Ottawa / University of Ottawa, 2011)
Employing the concepts of lifeworld (Lebenswelt) and system as primarily discussed by Edmund Husserl and Jürgen Habermas, this dissertation argues that the lifeworlds of Anglo-Indian and Goan Catholics in the Greater Toronto Area have permitted members of these communities to relatively easily understand, interact with and manoeuvre through Canada’s democratic, individualistic and market-driven system. Suggesting that the Catholic faith serves as a multi-dimensional primary lens for Canadian Goan and Anglo-Indians, this sociological ethnography explores how religion has and continues affect their identity as diasporic post-colonial communities. Modifying key elements of traditional Indian culture to reflect their Catholic beliefs, these migrants consider their faith to be the very backdrop upon which their life experiences render meaningful. Through systematic qualitative case studies, I uncover how these individuals have successfully maintained a sense of security and ethnic pride amidst the myriad cultures and religions found in Canada’s multicultural society. Oscillating between the fuzzy boundaries of the Indian traditional and North American liberal worlds, Anglo-Indians and Goans attribute their achievements to their open-minded Westernized upbringing, their traditional Indian roots and their Catholic-centred principles effectively making them, in their opinions, admirable models of accommodation to Canada’s system.
Keywords: Catholicism; Goans; Anglo-Indians; Migration; Lifeworld; Habermas; Religion